Transgression – Transdisciplinarity – Translation - Włodarczyk, Rafał (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2020)
Successive parts of the article deal with the development of disciplinary, inter- and transdicyplinary research and its mutual relations and conditions in a new scientific and social context connected with reflexive modernization. The author points to pedagogy as a discipline that can be a model of an institution of translation, a discipline located on the borderline of humanities and social sciences, integrating and studying the conditions for the transfer of disciplinary, inter- and transdisciplinary knowledge, and which can develop the knowledge necessary to educate in the field of inter- and transdisciplinary translation.
Keywords: pedagogy; reflexive modernization; interdisciplinary research; transdisciplinary research; translation; knowledge transfers; integration of scientific knowledge